Sustainable Development of Universities: International and Russian Practices - T. N. Gavrilyeva; Atsuko Sugimoto; Masahiko Fujii; Ryo Yamanaka; G. N. Pavlov; D. A. Kirillin (Высшее образование в России)
The introduction of the principles of sustainable development into the world system of higher education began 30 years ago. It is one of the global trends now. The accumulated international experience is quite extensive and could be used in the development of the national concept of sustainable development of Russian higher education. The article is devoted to the analysis of the sustainable development networks interactions in higher education in the world and in Russia. Special attention paid to various stability ratings of universities. The experience of sustainable program implementation has been revealed on the example of the University of Hokkaido, one of the seven national corporations in the system of higher education of Japan. The experience of energy and resource-saving measures in the North-Eastern Federal University (Yakutsk, Russia) including the energy performance contract, is presented. The necessity of actualization of the national project of sustainable development of higher education institutions of Russia and the development of a national rating of the sustainability adapted to the legal framework and budgeting is substantiated.